"I'm slowly ageing but I still have my value": challenging ageism and empowering older persons through lifelong learning in Singapore. Issue 10 (2nd October 2020) - Maulod, Ad; Lu, Si Yinn
ABSTRACT: The National Silver Academy (NSA) was launched in 2016 as part of the Singapore government's Action Plan for Successful Aging. This paper uses a grounded approach to explore and assess critical geragogical elements that are enabling, empowering and transformative for older learners. Semi-structured in-depth interviews were conducted with 48 participants who had completed an NSA course. Although three different categories of older learners were identified in this study, most tend to internalize ageism and took courses to counter ageist stereotypes of being frail, dependent and useless. In terms of geragogy, participants articulated four key learning needs at the NSA. These were: (i) relatable, empathetic and engaging instructors; (ii) interactive and versatile methods of teaching with emphasis on real-life applications; (iii) flexible and accessible curriculum and course content appropriate to learners' capabilities and expectations and (iv) inclusive and disability-friendly learning environments catering to a wide spectrum of learners. At the NSA, instructors are crucial to the empowerment of older learners by leading the challenge against ageism, promoting learners' confidence and self-worth as well as enabling safe spaces for personal transcendence and creative expression. This study reinforces the need for more contextualized models of geragogy to dismantle structural and internalized forms of ageism by taking into account older learners' cultural beliefs about aging, access to education, confidence and competences to navigate both formal and informal learning environments.